Legal Protection For Policyholders Against Breach Of Insurance Contract By Insurance Companies (Analysis Of Decision Number 662/Pdt.G/2023/PN Jkt.Sel) - Simanjuntak, Fadma Marcela; Nasution, Abdul Razak (Fakultas Hukum Dehasen, 2025)
Insurance is an activity established by an individual to cover losses or risks that may occur to those involved in an insurance program. As policyholders, we are required to pay premiums, and the insurance company is expected to fulfill its obligations according to the insurance policy agreement. The problems addressed in this study are: How is the legal regulation regarding breach of contract (wanprestasi)? How is legal protection for policyholders provided? How is the legal resolution of the breach of contract case by the insurance company in case number 662/Pdt.G/2023/Pn Jkt.Sel? This research employs a descriptive-analytical approach. The type of research used in this study is normative legal research, which relies on secondary data. The research method used is library research, involving a review of various sources such as court decisions, journals, expert opinions, scholarly articles, and other readings. Insurance companies committing breaches of contract can cause significant losses for policyholders, as breach of contract refers to the failure to uphold an agreement or violate previously made commitments. The occurrence of such breaches stems from various reasons within the company, leading to their inability to fulfill their obligations to policyholders.